Cell proliferation downregulated by TGF-β2-triggered G1/S checkpoint in clinical CAFs. Issue 2 (17th January 2017) - Wu, Jinliang; Fu, Rong; Liu, Zongzhi; Li, Guochao; Huang, Xiaolei; Xue, Yang; Xu, Yan; Sun, Yingli; Zhao, Jiangmin; Mi, Jun
ABSTRACT: The metabolic reprogramming is indispensible for the fast growth of tumor cells. The metabolism of CAFs is reprogrammed to aerobic glycolysis too. However, it is not clear whether this metabolic reprogramming promotes the growth of CAFs themselves. In this study, we found that the proliferation rate of CAFs was slower than NAFs, which was determined by cell counting, BrdU assay and flow cytometry analysis. Moreover, we found TGF-β signaling regulated cell growth of CAF through RNA-sequencing analysis and Western blot, which was further supported by the observation that TGF-β2 was highly expressed in colon cancer tissues. In the end, we demonstrated that CAFs were critical to tumor cell proliferation, which was supported by the evidence of their close localization in clinical tumor tissue and tumor promoting effect in mice. In brief, our data have manifested that the proliferation rate is decreased in CAFs, which enable CAFs generate more intermediate metabolites to support tumor cells growth, suggesting CAFs is an ideal target for tumor therapy.